(untitled) (Research, Society and Development, 2021)
The present study aimed to characterize the incidence and profile of newborns born (NB) with congenital malformations (CFM), as well as the associated maternal risks. The research took place by filling out the Malformations and Control Form 10.4 of the Operational Manual of the Latin American Collaborative Study of Congenital Malformations, based on the records of the hospital and maternity reference Dona Regina de Siqueira Campos, in the city of Palmas, Tocantins, in the period of 1 May to December 31, 2016. 204 binomial birth records (102 controls and 102 cases) were analyzed. An 8.7% incidence was identified with a higher prevalence of NB with male CFM in the musculoskeletal system, premature and with low birth weight. Significant differences showed an association with head circumference below the Z-score ≤ -2 (p<0.001). As for maternal risks, only mothers aged between 15 and 25 (p<0.01) had an association with NB with CFM. The study shows a high incidence of CFM and contributes to direct health surveillance regarding decision-making in planning health policies in the Women’s and Children’s Health area.